Elementary School Students’ Learning Activity in Pancasila Education Subjects through the Problem Based Learning Learning Model assisted by Wordwall Learning Media - Irawan, Dedy; Farachdila, Restu; Andriani, Ana; Febrianta, Yudha; Badarudin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
The low learning activity of students in Pancasila Education subjects in the fifth grade of SD Negeri 1 Karanggintung is the background of this study. Low learning activity occurs because the learning activities are still Teacher-centered. This study aims to improve student learning activity in the fifth grade of SD Negeri 1 Karanggintung in Pancasila Education subjects by using the Problem-Based Learning (PBL) learning model with the help of Wordwall learning media. This study uses the Classroom Action Research (CAR) model. Kemmis and Mc. Taggart is the reference in the implementation of two cycles. The data collection and analysis techniques used in this study are test and non-test techniques and data analysis from observations of student learning activities during learning activities. The results of the study in cycle I showed that the percentage of student learning activity was 62.50%, and in cycle II, it was 80.36%. The study concludes that using the Problem-Based Learning (PBL) learning model and Wordwall learning media can improve student learning activity in the fifth grade of SD Negeri 1 Karanggintung in the Pancasila Education subject. These classroom action research findings are that students appear more active and enthusiastic after learning activities are carried out using the Problem-Based Learning (PBL) model and Wordwall learning media.